1999
DOI: 10.1063/1.370800
|View full text |Cite
|
Sign up to set email alerts
|

Depth distribution of luminescent Si nanocrystals in Si implanted SiO2 films on Si

Abstract: Depth-resolved measurements of the photoluminescence of Si implanted and annealed SiO 2 films on Si have been performed to determine the depth distribution of luminescent Si nanocrystals. Si nanocrystals with diameters ranging from ϳ2 to 5 nm were formed by implantation of 35 keV Si ions into a 110-nm-thick thermally grown SiO 2 film on Si͑100͒ at a fluence of 6ϫ10 16 Si/cm 2 , followed by a thermal anneal at 1100°C for 10 min. The photoluminescence spectrum is broad, peaks at ϭ790 nm, and contains contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 22 publications
4
34
1
Order By: Relevance
“…The sizes of the nc-Si produced from the Gaussian ion implantation profile, were inferred from the variation of average PL emission wavelength with D, due to their size-dependent exciton emission energies, and found to be depthdependent. The measured trends indicated that smaller nanocrystals formed in the wings of the implanted excess Si + distribution, consistent with previous observations by Brongersma et al 6 The reference sample PL intensity, I PLref , was measured for each D, and the luminescence intensities were found to be consistent with a Gaussian nc-Si distribution centered at 19.2 ± 0.1 nm from the unetched surface. The separation distance between the quartz surface and the peak of the Si nanocrystal distribution at each step is therefore equal to (19.2 nm -D).…”
Section: Supporting Informationsupporting
confidence: 89%
“…The sizes of the nc-Si produced from the Gaussian ion implantation profile, were inferred from the variation of average PL emission wavelength with D, due to their size-dependent exciton emission energies, and found to be depthdependent. The measured trends indicated that smaller nanocrystals formed in the wings of the implanted excess Si + distribution, consistent with previous observations by Brongersma et al 6 The reference sample PL intensity, I PLref , was measured for each D, and the luminescence intensities were found to be consistent with a Gaussian nc-Si distribution centered at 19.2 ± 0.1 nm from the unetched surface. The separation distance between the quartz surface and the peak of the Si nanocrystal distribution at each step is therefore equal to (19.2 nm -D).…”
Section: Supporting Informationsupporting
confidence: 89%
“…The error bars are calculated by taking into account the straggle of the Si depth profile and assuming a symmetric spread of Si QDs around the center of the distribution. 34 The decay rate enhancement by the Ag is then a factor 2.1± 0.1, and is mostly due to the additional SP decay channel that constitutes 60% of the total decay rate. Experimentally, the decay rate enhancement derived in Sec.…”
Section: Modeling the Si Qd Decaymentioning
confidence: 99%
“…1,2 Recently, it has been proposed to use them in solar cells for down-conversion, to generate multi-excitons or as a top absorber in multifunction solar systems. [3][4][5][6][7] Several different methods for fabricating Si-NCs, all compatible with the semiconductor industry standards, have been developed, such as ion implantation, 8 cosputtering, 9 or plasma enhanced or low pressure chemical vapor deposition (CVD). 10 Even so, all these techniques face difficulties in accurately controlling the Si-NCs size and density, leading to a certain degree of uncertainty in interpreting how the actual Si-NCs morphology affects their electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been put so far to control the Si-NCs size, either by controlling the silicon concentration, the postdeposition thermal process [8][9][10] or limiting the thickness of SiO x layers between SiO 2 stoichiometric barriers (as the one proposed by Zacharias et al 11 ). Nevertheless, only few works can be found in literature dedicated to control and analyze the Si-NC areal density in similar systems.…”
Section: Introductionmentioning
confidence: 99%